SUSTAINABILITY ASPECT OF TOURISM DEVELOPMENT IN THE EAST AUKŠTAITIJA REGION, IN LITHUANIA - Narkūnienė, Ramutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The author of the paper discusses the tourism development from the sustainability aspect in the East Aukštaitija region, in Lithuania. The scientific problem - the tourism development trends have not been sufficiently studied at regional level in Lithuania and tourism in the regions developed without a clear long-term development strategy and consistent implementation of the programme. The aim of the research is to explore tourism development by sustainability aspect in the East Aukštaitija region, in Lithuania. Many scientists have analysed trends in sustainable tourism development. However, tourism development conditions at region level have not been researched, only sporadic research studies have been performed. The main problems of tourism development in the aspect of sustainability in the East Aukštaitija region are as follows: seasonality, lack of investment in sustainable tourism, lack of knowledge about the essence of sustainable tourism and the principles of local politics, undeveloped infrastructure. The most important activities for the development of sustainable tourism are the responsible tourist approach to the use of natural resources; investment in sustainable tourism development; tourism development, planning and control; legalization of sustainable tourism development in national strategic documents.